(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
An analysis was conducted of the effectiveness of the phytotherapeutic drug Sinupret in 55 patients who underwent surgical interventions on the nasal cavity and paranasal sinuses. Based on clinical observations and objective research methods, it was found that the inclusion of Sinupret in the comprehensive therapy of the early postoperative period promotes faster resolution of reactive changes in the nasal mucosa and reduces the severity of pain syndrome compared with conventional therapy.